FAKTOR-FAKTOR YANG MEMPENGARUHI KEHANDALAN NILAI INFORMASI KEUANGAN PEMERINTAH DAERAH - Yanto, Yanto (LPPM STIE Pertiba, 2019)
This study aims to determine whether the quality of human resources, the use of information technology, the internal control system, the field of financial control, and organizational commitment affect the reliability of the financial reporting information value of the Bangka Regency government. The sample amounted to 96 respondents in the government of Bangka Regency. The sample in this study used purposive sampling using the specified criteria. The type of data and data collection methods are primary data, research data obtained directly from the original source in the form of answers to the questionnaire. The results form factors, namely the internal control system and the financial control area. Where the form factor consists of variable quality of human resources, utilization of information technology, internal control systems, areas of financial control and organizational commitment have a significant influence on the reliability of the value of financial reporting information of local governments. The dominant variable is the internal control system, while the lowest variable is the quality of human resources.